Effects of Baffle Height and Baffle Location on Heat Transfer and Flow Profiles in a Baffled Duct: A CFD Analysis - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2022)
CFD analysis of flow and heat transfer characteristics in a baffled duct is reported. The baffle locations ( s = 0.05 H – 0.40 H ), flow paths (V-apex directing Downstream or VD and V-apex directing Upstream or VU), and baffle heights ( b = 0.05 H – 0.30 H ) are investigated in the laminar flow regime with the Reynolds number based on the entry conditions between 100 and 2,000. Solutions of the present work are obtained by the finite volume method (a commercial code). Key mechanisms such as fluid streams, impinging streams, and disturbed thermal boundary layer in the baffled duct are observed. The baffle locations have high impact on flow and heat transfer behavior. The best heat transfer rate of the baffled duct is 15.55 times higher than that of the general duct with no baffle, while the optimum TEF is 4.06.
Keywords: Baffle; Heat Transfer Mechanisms